2013
DOI: 10.1021/am400582n
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Pickering Emulsions Stabilized by Graphene Oxide

Abstract: Stable Pickering emulsions were prepared using only graphene oxide (GO) as a stabilizer, and the effects of the type of oil, the sonication time, the GO concentration, the oil/water ratio, and the pH value on the stability, type, and morphology of these emulsions were investigated. In addition, the effects of salt and the extent of GO reduction on emulsion formation and stability were studied and discussed. The average droplet size decreased with sonication time and with GO concentration, and the emulsions ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
315
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(337 citation statements)
references
References 49 publications
18
315
1
Order By: Relevance
“…For this system, an emulsion may need to be stabilised in work similar to that described by Zhou et al, who designed amphiphilic silica particles for the solvent-free acetalisation of long-chain fatty aldehydes with ethylene glycol [35]. In addition to this work, He et al has suggested that graphene oxide particles can also be used to stabilise emulsions of the oil-in-water type [36]. In this case, gold would need to be in a separate phase to the cyclohexene because of its high activity in cyclohexene oxidation, which could be achieved by the use of hydrophilic supports.…”
Section: Discussionmentioning
confidence: 99%
“…For this system, an emulsion may need to be stabilised in work similar to that described by Zhou et al, who designed amphiphilic silica particles for the solvent-free acetalisation of long-chain fatty aldehydes with ethylene glycol [35]. In addition to this work, He et al has suggested that graphene oxide particles can also be used to stabilise emulsions of the oil-in-water type [36]. In this case, gold would need to be in a separate phase to the cyclohexene because of its high activity in cyclohexene oxidation, which could be achieved by the use of hydrophilic supports.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the structure of single-layered Janus graphene nanosheets, stacked GO and the hybrid films with the thickness of several hundred nanometers or above were functionalized to achieve macroscopic films with asymmetric surfaces [47,48]. Hydrophilic oxygen-containing groups and hydrophobic basal plane endow GO with amphiphilicity to act as Pickering stabilizer [49,50]. Monolayer Janus GO is expected to show excellent ability to stabilize Pickering emulsions due to its asymmetric 4 surface wettability in comparison with homogeneous GO [14,16,51].…”
Section: Introductionmentioning
confidence: 99%
“…The highest amount of GO transfer was achieved for toluene (97.9 %), due to strong p-p interactions between the residual conjugate domain of the GO basal plane and aromatic toluene molecules, which facilitate the transfer of GO from water to toluene. [10,16] 97.6 % GO transfer was observed with kerosene, due to the aromatic molecules in its composition. Although carbon tetrachloride is nonaromatic, 27.7 % GO transfer was achieved with it, due to the possibility to form hydrogen bonds between the carboxylic hydrogen atoms of GO and the chlorine atoms of the solvent.…”
Section: Effect Of the Organic Solventmentioning
confidence: 99%